Multichannel system for research of secondary emission pulse electron beam generation - Ayzatsky, N.I.; Boriskin, V.N.; Gurin, V.A.; Kushnir, V.A.; Mitrochenko, V.V.; Reshetnyak, N.G.; Romas’ko, V.P.; Savchenko, A.N.; Zakutin, V.V. (Вопросы атомной науки и техники, 2004)
To carry out crossed-field secondary emission electron sources scientific-research developments we have designed and manufactured a 12-channel information measuring system. A hardware complex of the multichannel pulse-signal recording system is
built up from a personal computer, crate CAMAC with modules, an interface unit and a synchronization system. The software of
information measuring system operates in the Windows environment. Для дослідження вторинно-емісійних електронних гармат зі схрещеними полями нами була розроблена і
виготовлена 12-ти канальна інформаційно-вимірювальна система (ІВС). Програмно-технічний комплексмногоканальной системи реєстрації імпульсних сигналів складається з персонального комп'ютера, крейта КАМАК з
модулями, блоку сполучення і системи синхронізації. Програмне забезпечення ІВС працює в середовищі Windows. Для исследования вторично-эмиссионных электронных пушек со скрещенными полями нами была разработана и
изготовлена 12-ти канальная информационно-измерительная система (ИИС). Программно-технический комплекс многоканальной системы регистрации импульсных сигналов состоит из персонального компьютера, крейта КАМАК с модулями, блока сопряжения и системы синхронизации. Программное обеспечение ИИС работает в среде Windows.